2011
DOI: 10.1111/j.1365-313x.2011.04690.x
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of MYB factors in differential cell expansion, and consequences for tomato fruit development

Abstract: ). † These authors contributed equally to this work. SUMMARYWe previously identified SlFSM1 as an early fruit-specific gene encoding a short protein harboring a noncanonical SANT/MYB-like domain. Here, we investigated the role of FSM1 during fruit development in tomato and its mode of action. By analyzing tomato plants ectopically expressing FSM1, we established that it negatively affects cell expansion, particularly of those cells with the highest potential to expand, such as those residing inner to the vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 46 publications
3
85
1
1
Order By: Relevance
“…RAD binds to DRIF in competition with the DIV-DRIF interaction, promoting translocation of DRIF to cytoplasm and resulting in downregulation of DIV function. The same interaction mechanism for MYB proteins has been reported for RAD and DIV orthologs in tomato during fruit development (Machemer et al, 2011). In our results, differences between dorsal and ventral petals in TfDIV expression were less clear than those for TfCYC1, 2, and 3 and TfRAD1 in NT flowers (Figs.…”
Section: Structure and Expression Analyses Of Floral Symmetry Associacontrasting
confidence: 47%
See 1 more Smart Citation
“…RAD binds to DRIF in competition with the DIV-DRIF interaction, promoting translocation of DRIF to cytoplasm and resulting in downregulation of DIV function. The same interaction mechanism for MYB proteins has been reported for RAD and DIV orthologs in tomato during fruit development (Machemer et al, 2011). In our results, differences between dorsal and ventral petals in TfDIV expression were less clear than those for TfCYC1, 2, and 3 and TfRAD1 in NT flowers (Figs.…”
Section: Structure and Expression Analyses Of Floral Symmetry Associacontrasting
confidence: 47%
“…Phylogenetic analysis of the deduced amino acid sequences of these genes and those of the orthologs in other plants showed that the torenia genes were highly similar to the orthologs of A. majus ( Fig. 3a, b; Barg et al, 2005;Baxter et al, 2007;Machemer et al, 2011;Martín-Trillo and Cubas, 2010). The TCP domain for DNA binding activity, R domain involved in the CYC/TB1 family of TCP genes, and ECE motif were conserved in TfCYC1, 2, and 3 ( Fig.…”
Section: Structure and Expression Analyses Of Floral Symmetry Associamentioning
confidence: 98%
“…In T. fournieri , regulation of TfCYC2 by TfRAD1 was probably indirect, as we failed to detect the DNA‐binding activity of TfRAD1 in a random binding site selection experiment (data not shown), which was consistent with previous work in snapdragon and tomato (Machemer et al ., ; Raimundo et al ., ). In tomato, both RAD‐like SlFSM1 and DIV‐like SlMYB1 interact with another MYB factor, SlFSB1, revealing the competitively interactive behavior of a RAD‐like factor on a post‐translational level (Machemer et al ., ). In snapdragon, RAD cannot recognize the DNA‐binding site of DIV, and does not prevent DIV from binding to the I‐box sequence (Raimundo et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Both AtMYB124 and AtMYB88 encode R2R3 MYB transcription factors, which are expressed during ovule development and have been identified to regulate female reproductive development45. SlFSM1 encodes a SANT/MYB-like domain and is an early fruit-specific gene, and the SlFSM1 / FSB1 / MYBI complex controls cell expansion and fruit development in tomato46. Furthermore, most known regulators of fruit development such as SPT , IND , CRC , FUL , SUP and HAN were transcription factors that were differentially expressed between lines 408 and 409, and many of them can mediate cell division and expansion3637384042.…”
Section: Discussionmentioning
confidence: 99%